Supremasi Hukum dalam Masyarakat Madani - Akh Minhaji (Universitas Islam Indonesia, 2000)
The process of civil society establishment requires some social prerequisites, namely the Law supremacy. The writer of this book tries to apply the egality and the inclucivism of Islamis Law to support the establishment of the democratic society based on the diversity and the humanity. Having religion as the fundamental factor of the Law supremacy will lead Indonesia to find the solution of the social and ecomic problems arising as a result of the social changes in the reformation process.